Granulocyte Colony-Stimulating Factor Use in a Large Iranian Hospital: Comparison with American Society of Clinical Oncology (ASCO) Clinical Practice Guideline - Sarah Mousavi; Mina Dadpoor; Farzaneh Ashrafi (International Journal of Hematology-Oncology and Stem Cell Research, 2016)
Background: Granulocyte Colony Stimulating factors (GCSF) are high cost agents commonly recommended for primary and secondary prophylaxis of chemotherapy-induced neutropenia and febrile neutropenia. GCSFs have been shown to be beneficial in some patient subgroups, although they are probably overused in clinical settings. The American Society of Clinical Oncology (ASCO) guidelines summarize current data on the appropriate use of CSFs. The objective of this study was to assess and audit the use of GCSF in a tertiary care center according to recommendation of ASCO guideline. Methods: A Retrospective observational study from November 2014 to June 2015 was performed on all patients prescribed with filgrastim in the large teaching hospital (Isfahan, Iran). Data was collected on demographics, indication, dosing regimen, duration of treatment, the Absolute Neutrophil Count (ANC) and patient outcome. Results: 91 patients were recorded over the period of the study. 63.7% of prescription complied with the ASCO guideline. Febrile neutropenia post chemotherapy/radiotherapy was the most common appropriate indication (29.3%) followed by primary prophylaxis (25.8%). Fourteen (32 %) patients showed ANC recovery in 1-3 days, and 16 (37%) within 4-7 days. Ten patients (23 %) showed no recovery. The overall mortality was 8 (8.8%) patients. Conclusion: This study revealed that at least one-third of prescribed GCSF was not in accordance with ASCO guideline. Considering the high cost of GCSF in our country and limitation of our resources, we proposed cost-effectiveness studies on GCSF treatment and also development of national guideline for optimizing GCSF use.